PELATIHAN PROGRAMMING BAHASA INGGRIS KEPADA ANAK-ANAK DI SEKOLAH OPEN FLOW - I Gde Agoes Caskara Surya , Putra,; Ni Wayan, Suastini,; Ida Bagus Kade , Widiartana, (LOKATARA SARASWATI, 2024)
Open Flow Learning Centre is to help develop children's values, attitudes, skills, and knowledge through our interconnectedness with nature and one another. These foundations are applied and delivered through the basis of Inquiry, STEAM (Science, Technology, Engineering, Arts, Mathematics), and Project-Based Learning by providing a coding class that is aimed at enhancing English language learning through innovative methods. The project involved integrating coding principles and RPG Maker, a game development platform, to create an engaging and interactive learning environment for Indonesian children. By utilizing coding techniques within RPG Maker, children could design and develop their own digital games while simultaneously practicing English language skills. The project's objective was to explore the potential of technology-driven education in improving language learning outcomes. This article discusses the process of implementing the initiative, the impact on language learning, and the role of technology in fostering creativity and engagement among the participants. The findings suggest that combining coding and RPG Maker can be an effective approach to fostering language learning in a playful and dynamic manner, catering to the needs and preferences of young learners. This initiative sheds light on the viability of integrating technology and creative platforms as tools to augment language acquisition among children. Keywords: Coding, RPG Maker, English language learning, community service, technology-driven education.